O conceito de pessoa com deficiência e as repercussões no direito brasileiro - Ovalle, Maytê (Universidade do Vale do Rio dos Sinos, 2020)
This dissertation analyses concepts of disability and their influence on unequal treatment among persons with disabilities (PWD). This study explores the concept of disability and its impact on material equality provided by the Brazilian Federal Constitution and has its main objective is to analyze the unequal treatment of single-sided deafness and vision by the Brazilian Judiciary. This study will consider the matter of the Decree 3,298/99 and its literal interpretation. The initial hypotheses were: a) negative, considering that the unequal treatment is legitimate, well-founded, and legal, with no associated subjective factors and that, therefore, there is no need to discuss limiting material equality between disabilities; and b) positive, in the sense of the illegitimacy of the difference in treatment originating from the literal interpretation of Decree 3,298 / 99, the result of a subjective factor of the judge, so that its limitation undermines the achievement of material equality to groups with disabilities other than those determined by it. This study was conducted through bibliographic and documentary research using a deductive and qualitative methodology for exploratory purposes. The in-depth study of the issue brought to light the incongruity of the Decree with the rest of the normative system in a way that literal interpretation becomes impossible when considering the enactment of international norms and legislative instruments that bring a more comprehensive and humane view of the person with disabilities and further emphasizes the incongruity within the Legislative Decree itself, concluding that the Article 4th of Decree 3,298/99; Binding Precedents No. 377 and No. 552 and sentences handed down after July 9th, 2008, involving unequal treatment between people with single-sided deafness and monocular blindness are unconstitucional.
Keywords: Deficiência; Surdez Unilateral; Hermenêutica; Disability; Single-sided deafness; Hermeneutics; ACCNPQ::Ciências Sociais Aplicadas::Direito